Reproductive phenology differs between evergreen and deciduous species in a Northeast Brazilian savanna - Assuncao Lacerda, Dinnie Michelle (2018)
Evergreen (EG) and deciduous (DEC) species exhibit distinct strategies to overcome dry periods and achieve adequate water status for reproduction and growth. Such particularities may result in distinct reproductive strategies between these groups. Thus, we evaluated the phenology of EG and DEC groups, comparing and differentiating their reproductive phenophases in an area of Brazilian savanna (cerrado sensu stricto), located in Mirador State Park, Maranhao State, by associating these patterns with leaf fall and flushing. Leaf fall, leaf flushing, flowering and fruiting data were monitored between April 2014 and March 2016 for 12 EG and 13 DEC species. To assess differences in flowering and fruiting patterns between EG and DEC, we compared phenological time, activity and intensity, and the duration of phenophases. We found earlier occurrence and longer duration of flowering for EG than for DEC; for fruiting, EG differed from DEC in activity throughout the year, with the intensity being greater for the EG group. These responses may reflect the distinct water-use strategies adopted by the EG and DEC groups, and confirm that differences in their ecophysiological strategies may exert an influence on their reproductive phenology.